Analisis Faktor – Faktor yang Mempengaruhi Tingkat Pendapatan Pemilik Usaha Industri Kecil-Menengah (Studi Kasus Industri Kecil-Menengah Makanan Ringan di Desa Talok Kecamatan Turen Kabupaten Malang) - Unda ikmana Dean Prisatya (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aims to determine the effect of  financial capital, the amount of labor, and business experience on  income level of small and medim industrial owners with case study on small and medium snacks industrial in Talok village. This research quantitative data used are primary data. Method of regression analysis using doubled regression and transformed into log-linier regression. Research  results  showed  that simultaneous  financial capital,  the amount of labor, and business experience  has  a significant effect on  the variable  income level.  In  partial  income level significantly affected by  financial capital(+),  the amount of labor(+), and business experience(+) on  income level  of small and medim snacks industrial in Talok village. The rate  coefficient of determination  ( )  for the variables  that affect working income level amounted to 95.8%, which means  the independent variables  in the model is able to explain  the dependent variable  (income level) at 95.8%, the remaining 4.2% is explained by variables outside this model.Keywords : Income Level, Financial Capital, Labor, Business Experience